Network Qos architecture - Mahmoud, Omer; Anwar, Farhat; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Saeed, Rashid A. (IIUM Press, 2011)
There is huge growth in internet recently. This growth is started initially at slow rate with limited number of application, However as the time progresses the nehvork has expanded in term of users and applications, This expansion dictated a alteration and modification of the original protocol to enable higher Quality of service. This chapter provides tan over view about QoS requirement, architecture and mobility support